1996
DOI: 10.3109/10428199609067585
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Delivery of Oligodeoxynucleotides

Abstract: We have previously demonstrated that liposome-incorporated methylphosphonate antisense oligodeoxynucleotides (oligos) specific for BCR-ABL can selectively inhibit the expression of p210Bcr-Abl protein and the proliferation of chronic myelogenous leukemia cells in vitro. Here, we show that liposome-entrapment of phosphodiester and phosphorothioate oligos specific for BCR-ABL can also selectively inhibit the proliferation of chronic myelogenous leukemia cells. We have studied the intracellular localization of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…We have previously demonstrated that neutral nanoliposomes are effective carriers for nucleotides in diverse animal models [117–120]. A DOPC loaded with antisense oligonucleotides against Grb2 is currently in advanced phase I clinical trial in leukemia [121], and no safety issues have been observed in this trial so far.…”
Section: Targeting Epha2 With Sirna-based Therapeuticsmentioning
confidence: 99%
“…We have previously demonstrated that neutral nanoliposomes are effective carriers for nucleotides in diverse animal models [117–120]. A DOPC loaded with antisense oligonucleotides against Grb2 is currently in advanced phase I clinical trial in leukemia [121], and no safety issues have been observed in this trial so far.…”
Section: Targeting Epha2 With Sirna-based Therapeuticsmentioning
confidence: 99%
“…Encapsulation or incorporation in liposomes is currently the preferred method for the delivery of AS ODNs [21,29,32,41,45,[59][60][61][62][63][64][65][66][67][68][69] and, besides the intravenous infusion and subcutaneous, intramuscular or intraocular injection of naked ODNs, probably the only other method used in human clinical trials. (Ultimately, the suspensions of liposomes are also administered by infusion or injection.)…”
Section: Delivery Of As Odns: the Current Statusmentioning
confidence: 99%
“…9 Encapsulation of DNA into liposomes, however, has proved technically difficult, frequently resulting in entrapment efficiencies of <50%, 10 although there are a few exceptions. 9,11 To improve the incorporation of plasmid DNA, cationic lipids have been developed which, when incorporated into liposomes, can efficiently complex negatively charged DNA. Provided that the liposomes used also contain appropriate neutral lipids, such as dioleoylphosphatidylethanolamine (DOPE), the resulting complexes have been found to be effective for transfection in vitro [12][13][14][15][16] and in vivo.…”
Section: Introductionmentioning
confidence: 99%